2013
DOI: 10.1175/jcli-d-12-00678.1
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean Variability in the CMIP5 Multimodel Ensemble: The Basin Mode

Abstract: This study evaluates the simulation of the Indian Ocean Basin (IOB) mode and relevant physical processes in models from phase 5 of the Coupled Model Intercomparison Project (CMIP5). Historical runs from 20 CMIP5 models are available for the analysis. They reproduce the IOB mode and its close relationship to El Niño–Southern Oscillation (ENSO). Half of the models capture key IOB processes: a downwelling oceanic Rossby wave in the southern tropical Indian Ocean (TIO) precedes the IOB development in boreal fall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 84 publications
4
54
1
Order By: Relevance
“…10 The linear trend of a wind effect on latent heat flux from atmospheric forcing part (Q E W , colors, Wm −2 /10 yr) and surface wind (vector, ms −1 /10 yr), c SST (colors, K/10 yr) and surface wind (vector, ms −1 /10 yr), e sea surface height (SSH, colors, cm/10 yr) and surface wind (vector, ms −1 /10 yr), and g precipitation (colors, mmd −1 /10 yr) and surface wind (vector, ms −1 /10 yr) from ensemble means of the all-forcing runs from 16 CMIP5 models during the northern TIO and the northwesterly anomalies reduce the southeasterly trades over the southern TIO, which are favorable for the non-uniform IOBM-like warming pattern. As stated by Du et al (2013), the anomalous SST warming over the south TIO induced by the down-welling ocean Rossby wave and enhanced atmospheric advection with positive precipitation anomalies (Fig. 10h), reflecting the slowdown of the Walker circulation under global warming Vecchi et al 2006), trigger the anti-symmetric atmospheric circulation.…”
Section: Physical Mechanisms For the Double-peak And Non-uniform Iobmmentioning
confidence: 64%
“…10 The linear trend of a wind effect on latent heat flux from atmospheric forcing part (Q E W , colors, Wm −2 /10 yr) and surface wind (vector, ms −1 /10 yr), c SST (colors, K/10 yr) and surface wind (vector, ms −1 /10 yr), e sea surface height (SSH, colors, cm/10 yr) and surface wind (vector, ms −1 /10 yr), and g precipitation (colors, mmd −1 /10 yr) and surface wind (vector, ms −1 /10 yr) from ensemble means of the all-forcing runs from 16 CMIP5 models during the northern TIO and the northwesterly anomalies reduce the southeasterly trades over the southern TIO, which are favorable for the non-uniform IOBM-like warming pattern. As stated by Du et al (2013), the anomalous SST warming over the south TIO induced by the down-welling ocean Rossby wave and enhanced atmospheric advection with positive precipitation anomalies (Fig. 10h), reflecting the slowdown of the Walker circulation under global warming Vecchi et al 2006), trigger the anti-symmetric atmospheric circulation.…”
Section: Physical Mechanisms For the Double-peak And Non-uniform Iobmmentioning
confidence: 64%
“…As a consequence, the dissipation of the WP events seems to occur via ocean heat discharge, in a similar way to CT events, rather than via advection of mean SST gradients by anomalous zonal currents as seen in observations. Recent studies have also attributed biases in ENSO simulations to remote influences, particularly climate over the Indian Ocean basin (Du et al 2013;Santoso et al 2012, and references therein). Okumura and Deser (2010) suggest that remote forcing from the Indian Ocean can influence the asymmetry in the duration of El Niño and La Niña.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Du et al (2013) suggested that half of CMIP5 models capture the key processes responsible for TIO basin-wide warming associated with El Niño. Saji et al (2006) found that the association between El Niño and TIO basin-wide warming is well resolved in many of the CMIP3 models.…”
mentioning
confidence: 99%